PENGARUH PENGALAMAN KERJA, INDEPENDENSI, DAN OBYEKTIVITAS AUDITOR TERHADAP KUALITAS HASIL PEMERIKSAAN PADA INSPEKTORAT PROVINSI SULAWESI SELATAN - Nur Fatwa Basar (AkMen JURNAL ILMIAH, 2015)
Effect of Work Experience, Independence and Objectivity Auditors on the Quality Inspection Results in south Sulawesi Provincial Inspectorate. This study aimed to analyze the effect of work experience, independence, objectivity of the auditors on the quality Inspection results of the inspectorate South Sulawesi, and to analyze which variables are the dominant effect. Collecting data using questionnaires distributed to 93 respondents, while as many as 73. The questionnaire returns Of these respondents, there are 42 people or 57.53% over 40 years old, while the remaining <40 years. Male respondents as many as 48 people or 65.75% and women by 25 people, or 34.25%. Working period 1-10 years as many as 33 people or 45.21%, and 55.79% over the service life of 10 years. Class III as many as 53 people (72.60%) while the rest Class I, II, and IV. S1 education level as many as 45 people or about 61.64%, while the rest of high school education, Diploma, S2. Training of the most widely followed as much as 2 times the number of 24 people (32.88%). The results showed that either simultaneously or in partial, Work Experience, Independence and Objectivity positive and significant impact on the quality of the results of the Inspectorate of South Sulawesi province. Thus, the first hypothesis is proven research. Of the three independent variables used in the quality of the examination, the independence of the variables have a dominant influence on the quality of the results of the Inspectorate of South Sulawesi province. Thus, the second hypothesis of this study proved.